The Developing of Using Cardboard Media into a Patience Rocket to Improve the Social and Emotional Abilities of Children Aged 4-5 Years at Kindergarten Dharma Wanita - Usnul Khotimah; Leli Fertiliana Dea; Isnaini Nur Azizah; Masrurotul Mahmudah; Muhammad Yusuf (Bulletin of Pedagogical Research, 2024)
This research is to develop of using cardboard into patience rockets for children aged 4-5 years at Dharma Wanita Kindergarten. The researchers use R&D (research and development) research with the ADDIE (Analysis, Design, Development, Implement and Evaluation) development model. Collecting data use questionnaires, observation, interviews and documentation. The results of this research are the development of used cardboard into patience rockets for children aged 4-5 years at Dharma Wanita Kindergarten, namely with the following steps: validation results from media experts assessing the patience rocket media with a percentage of 90% or very feasible category, then material experts It can be seen that the material on the patience rocket media is completely in accordance with the material indicators with a percentage of 100% or in the very feasible category. The effectiveness of using the patience rocket media in improving the social emotional aspects of children aged 4-5 years at Dharma Wanita Kindergarten. This was proven before implementing the patience rocket media, out of a total of 12 children, it was known that 6 children's social emotional abilities were in the Not Developed category. This can be seen from the ability of children who have not shown an independent attitude, lack of self-confidence and children who do not understand rules and discipline, 6 children in the Starting to Develop category. Then, after applying the patience rocket media, it was discovered that 4 children were starting to develop. Children no longer need teacher assistance and 1 child is developing very well. Therefore, in this research it can be said that the patience rocket media is effective in improving children's social emotional abilities.